Institutional ownership and earnings quality pre- and post-IFRS - Alhadi, Saleh M. A. Abd; Senik, Rosmila; Johari, Jalila (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study investigates whether earnings quality (EQ) has improved after the adoption of International Financial Reporting Standards (IFRS) in Malaysia. It also examines whether institutional ownership is related to higher EQ and whether IFRS adoption moderates this association. Using a system generalized method of moments (GMM) on a sample of 1960 firm-year observations over the period 2007–2016, we find that EQ is significantly enhanced after adoption of IFRS in Malaysia. The findings also show that institutional ownership has a negative impact on accrual earnings management, leading to high EQ. This impact increased after IFRS adoption, indicating that institutional ownership is effective in improving EQ after IFRS compared to pre-period. Our findings indicate that regulators and practitioners should focus on institutional ownership and IFRS as monitoring mechanisms that remain an essential determinant of EQ.